2015
DOI: 10.1007/s11906-015-0573-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Measurement of Central Blood Pressure have Treatment Consequences in the Clinical Praxis?

Abstract: Interest in relations between central aortic pressure and cardiovascular disease risk has increased markedly over the past two decades. Numerous studies have shown that higher pulse pressure is associated with increased risk. Further, pulse pressure differs variably and sometimes dramatically between the central aorta and the brachial artery, where blood pressure is generally measured. In light of the potential for variable misclassification of central systolic and pulse pressure by brachial measurements, cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
1
8
0
3
Order By: Relevance
“…3,4 A VOP, um marcador de dano vascular utilizado na avaliação de rigidez arterial, é considerada um forte marcador independente de LOA e eventos adversos. 5 A VOP também é um preditor de mortalidade por todas as causas, indicando o risco real do paciente. 6 O aumento de um metro por segundo (1m/s) na VOP leva a um aumento de 14% no risco de eventos adversos e de 15% no risco cardiovascular e mortalidade por todas as causas.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…3,4 A VOP, um marcador de dano vascular utilizado na avaliação de rigidez arterial, é considerada um forte marcador independente de LOA e eventos adversos. 5 A VOP também é um preditor de mortalidade por todas as causas, indicando o risco real do paciente. 6 O aumento de um metro por segundo (1m/s) na VOP leva a um aumento de 14% no risco de eventos adversos e de 15% no risco cardiovascular e mortalidade por todas as causas.…”
Section: Introductionunclassified
“…PWV, a vascular damage biomarker used to assess arterial stiffness, is considered a strong and independent marker of TOD and adverse events. 5 PWV is also a predictor of all-cause mortality, indicating the patient’s actual risk. 6 Each one meter per second rise in PWV leads to an increases by 14% in the risk of adverse events and by 15% in the cardiovascular risk and all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The value of considering cSBP apart from pSBP has been discussed and considered over the last two decades. It has been stated that their association a-priori limits the incremental clinical value of cSBP[32]. However, it has been demonstrated that the association could be modified by the measurement procedure and particularly by the calibration method[8,27,28,33].…”
Section: Discussionmentioning
confidence: 99%
“…Wave reflection amplifies the original forward wave amplitude at or near the peripheral reflection site and therefore is a major determinant of PP and SBP . With increasing arterial stiffening, the reflected waves will return to the central aorta earlier and augment central PP and SBP . Increased wave reflection contributes to the development of hypertension and increases cardiovascular risk independently of arterial stiffness .…”
Section: Discussionmentioning
confidence: 99%